(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
Probiotic formulation is useful in reducing symptoms of irritable bowel syndrome. To assess effectiveness of multistrain probiotics with standard treatment than standard treatment alone. This was a randomized control trial conducted in the Department of Gastroenterology, BSMMU, from July 2015 to June 2016. Patients with diagnosed case of IBS using Rome III criteria, absence of red flag sign like anemia, fever, weight loss, per rectal bleeding, nocturnal frequency, family history of IBD, cancer and age 18-55 years, no probiotics used in prior 3 months were included in the study. Patients were divided into group A (Standard treatment) and group B (Probiotics with standard treatment). Symptom severity scores especially for abdominal pain, global symptom severity were assessed at baseline, at one month interval during treatment for two months and one month post treatment. Mean age of the patients was 31.64 ± 9.72 years and 32.17 ± 10.03 years with no statistical significant difference with male female ratio of 4.2:1 and 3.06:1 in group A and group B respectively. Severity of abdominal pain, frequency of pain in every 10 days, severity of abdominal distension, satisfaction with bowel syndrome, frequency of open bowels per day gradually reduced in both groups but was higher in group B than group A (P<0.05). Passing mucus with motion was gradually reduced in both groups but the decrement was higher in group A than group B (p<0.05). Multistrain probiotics with standard treatment is more effective in reducing IBS symptoms than standard treatment alone. JCMCTA 2016 ; 27 (2) : 31- 38